2005
DOI: 10.20420/rlfe.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Affective Variables in Second Language Acquisition and their Effect on the Spanish Academic Context

Abstract: For many students, learning a Second Language (SL) can either be a rewarding or a threatening experience. Recent studies claim that this is caused by the role that the affective domain plays in the learning process. Since the affective variables are considered the least understood by researchers in Second Language Acquisition (SLA), this paper focuses on them. The main purpose in this research is to study the connection among anxiety, attitude and motivation and their effect on the academic performance of sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In addition, the variable of language attitude affects (56.2%) of the English language learning and its acquisition as a foreign or second language, and this also goes in the same direction with some previous studies such as (e.g. Alkaabi, 2016;Moskovsky & Alrabai, 2009;Muñoz& Martí n 2015;Ranjabar & Narafshan, 2016). Furthermore, the variable of language self-confidence affects (57.4% %) of the English language learners' proficiency and acquisition, and this is also consistent with the results of previous research (e.g.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, the variable of language attitude affects (56.2%) of the English language learning and its acquisition as a foreign or second language, and this also goes in the same direction with some previous studies such as (e.g. Alkaabi, 2016;Moskovsky & Alrabai, 2009;Muñoz& Martí n 2015;Ranjabar & Narafshan, 2016). Furthermore, the variable of language self-confidence affects (57.4% %) of the English language learners' proficiency and acquisition, and this is also consistent with the results of previous research (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, some studies demonstrated the connection among anxiety, attitude and motivation and their effect on the academic performance of the L2 (ESL/EFL) learners (e.g. Muñoz and Martí n 2015). In addition, one study (Ranjabar and Narafshan, 2016) investigated the relationship between teachers' affective factors (motivation, anxiety, attitude, and self-confidence) and students' motivation in EFL classrooms.…”
Section: Attitudes Towards L2 (Esl/efl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive effects of foreign language anxiety were captured well by Krashen (1980) who noted that anxiety contributes to an affective filter (i.e., a mental block) which prevents learners from achieving a high level of proficiency in a foreign language (see also Brown, 1973;Muñoz & Ortega Martín, 2015). Horwitz, Horwitz and Cope (1986) emphasize that it is important for language teachers and students to identify the symptoms and consequences of foreign language anxiety since "the problem of anxiety and the accompanying erroneous beliefs about language learning … represent serious impediments to the development of second language fluency as well as to performance" (1986, p. 125).…”
Section: Introductionmentioning
confidence: 89%
“…Stress can be perceived as detrimental when it comes to both the teaching and learning process and to reduce stress, psychological capital should be raised in teachers. Hence, when stress is felt by teachers while working and when they feel ill-being, it will negatively affect students’ academic and behavioral outcomes [ 2 , 3 ]. Recent attention has centered on positive psychological capital in teachers [ 4 ], and a growing number of these studies suggested that teacher frustration could affect work engagement (WE) and lead to mental health problems [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%